The Effect of Pilgrimage to Waliyullah's Tomb on the Spiritual Motivation Student of Jagad 'Alimussirry - Ani Mahmudah; Djoko Hartono (Journal Intellectual Sufism Research (JISR), 2022)
The modern world, which is full of increasing human needs, is more easily met with the rapid advancement of science and technology. However, in reality the desired happiness is getting further away and causes a spiritual crisis. As for the signs of a spiritual crisis, material difficulties are replaced by mental difficulties which cause the mental burden to become heavier, anxiety and tension and feeling pressure are felt more often and are more pressing, thereby reducing happiness. Making a pilgrimage to the tomb of waliyullah’s is like being in the house of someone who is loved by Allah so that it can be a medicine for those who make pilgrimages and understand their pain and suffering. There he complained about all the problems he faced. In that house, he will feel at ease because he feels no longer alone and is under the auspices of Allah's grace and power. The results of previous research related to the research to be carried out are Fitriana's Thesis, (2014) entitled The Impact of Pilgrimage to the Tomb of Habib Sholeh Tanggul on Community Morals, and Selvi Raudatut Tilawah's Thesis, (2015) entitled Study of Living Hadith: The Phenomenon of Pilgrimage to the Grave in Village Author Kab. Bondowoso. so the author is interested in researching and studying more deeply about this problem by proposing the title of the research, namely the influence of pilgrimage to the tomb of waliyullah’s on the spirituality student of Jagad ‘Alimussirry. This type of research includes quantitative research that collects, collects and processes data in numerical form. The target population of the researcher is the active students of the Jagad 'Alimussirry Islamic Boarding School. Collecting data using questionnaires and interviews.